Semipolar GaN‐based heterostructures on foreign substrates. Issue 1 (30th September 2015) - Scholz, Ferdinand; Caliebe, Marian; Gahramanova, Gulnaz; Heinz, Dominik; Klein, Martin; Leute, Robert A. R.; Meisch, Tobias; Wang, Junjun; Hocker, Matthias; Thonke, Klaus
Abstract: This paper reviews our recent investigations about semipolar GaN‐based optoelectronic heterostructures grown on foreign substrates. Two basically different approaches are discussed, both making use of epitaxial growth in the polar c ‐direction to minimize any crystalline defects. By selective area growth, stripes with triangular cross‐section have been formed with semipolar side‐facets, on which quantum well and electroluminescence test structures have been deposited. By careful optimisation of many growth parameters, we could drastically increase the growth temperature of GaInN quantum wells emitting beyond 500 nm. In the second approach, the GaN growth starts on inclined sapphire c ‐planes, which form the side facets of trenches etched into the substrates. After coalescence, planar semipolar GaN layers can be achieved. We investigated various sapphire wafer orientations leading to { 11 2 ‾ 2 }, { 10 1 ‾ 1 }, and { 20 2 ‾ 1 } layers. After careful optimisation with a major focus on the decrease of the stacking fault density, we have also investigated the doping behaviour of such semipolar structures. Eventually, full electroluminescence test structures could be grown. Abstract : In order to solve issues related to huge internal electrical fields in GaN‐based optoelectronic device structures, less polar structures show very promising properties. This Feature Article reviews the authors' recent activities on this field concentrating on two different approaches: On the one hand, triangular stripes with semipolar side‐facets can be formed by selective area growth on conventional c ‐plane sapphire wafers. On the other hand, high‐quality planar semipolar structures are deposited on stripe‐patterned sapphire wafers.